EFFECT OF Cr AS A GRAIN GROWTH INHIBITOR ON CRYSTALLIZATION KINETICS FOR Fe73.5-xCrxCu1Nb3Si13.5B9 (x = 1, 5, 10, 12.5, 17.5) (Bangladesh Journal of Physics, 2025)
Nanocrystalline Finemet© alloys of composition Fe73.5-xCrxCu1Nb3Si13.5B9 with x = 1, 5, 10, 12.5, 17.5 were synthesized using the melt spinning technique to study the impact of chromium (Cr) as a grain growth inhibitor on the crystallization kinetics. The alloys were studied under several heat treatments starting from the as-cast to 600℃ and the amorphousity of the ribbons is reduced as well as the nucleation of crystallizations starts. Differential Scanning Calorimetry (DSC) analysis shows that increasing Cr content shifts the crystallization temperatures to higher values, enhancing thermal stability. Moreover, the X-ray diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM) confirmed the development of an ultra-fine α-Fe(Si) nanocrystalline phase, with the grain size decreasing as Cr content increased. The evolution of microstructure and thermal properties highlight the role of Cr content in delaying crystallization and reducing grain growth, thus improving the nanocrystalline state of the material. These findings provide insights into optimizing Fe-Si-B-based nanocrystalline alloys for advanced applications by balancing thermal treatments and Cr concentration.Bangladesh Journal of Physics, 28(1), 59-68, June 2021